Risk factors for pterygium in the Ambato population. Ecuador - Chabely Figueredo Morales; Tania Morales Molina; Yuleydi Alcaide Guardado (Medisur)
Foundation: pterygium is one of the most frequent ophthalmological conditions worldwide, its early diagnosis and its behavior knowledge is crucial. Objective: to determine the pterygium’s risk factors in patients seen in the ophthalmology clinic of the Ambato Municipal Hospital, Ecuador. Methods: a cross-sectional descriptive observational study was carried out from April 1 to 30, 2023. The population consisted of 483 patients who attended the ophthalmology clinic of the Ambato Municipal Hospital, Ecuador and the sample was selected at convenience and was made up of 161 patients. The analyzed variables were: age, sex, reason for consultation; job; object used to protect oneself from the sun. Results: pterygium was the main reason why the patients went to the ophthalmology consultation. There was a predominance of patients over 40 years old and male. 58.3% of patients with pterygium carry out jobs in which they are exposed to risk factors (farmer: 39.2%; driver: 14.9%; builder: 10.5%); More than a third of patients do not use any object to protect themselves from the sun. Conclusions: the pterygium appearance was found to be associated with people exposed to risk factors and linked to the male sex.